How Can Collaborative Circular Economy Practices in Modular Construction Help Fédération Internationale de Football Association World Cup Qatar 2022 to Achieve Its Quest for Sustainable Development and Ecological Systems? - Kucukvar, Murat; Kutty, Adeeb A.; Onat, Nuri C.; Al Jurf, Nasser; Al-Abdulmalek, Noora; Naser, Ayman; Ermolaeva, Yulia (Frontiers in Sustainability, 2021)
Embarking on the world cup journey with circular collaborative strategies can positively impact the environment and socio-economic outcomes to prosper development at the center of sustainability. World cup mega-events are set with overriding priorities in cutting down environmental footprints to accelerate sustainable development across the FIFA movement to leave an enduring legacy post-event in global sports. This paper conducts the first of its kind comprehensive critical analysis on ecological quality in life cycle impact assessment for 2022 FIFA World Cup modular container stadiums in Qatar. A "cradle-to-cradle" life cycle assessment, including the material and resource production, construction, operation, and end-of-life phase, is analyzed in this study, taking the case of Ras Abu Aboud stadium. Ecoinvent v3.7.1 life cycle inventory database was used to quantify the ecosystem damage-related impacts. Two scenarios were considered for the operation phase; scenario 1 (single year of operation) and scenario 2 (30 years of operation). A sensitivity analysis was used to understand the extent of impact per category indicator subject to material quantity variations. The results showed that the planned circularity contributed to savings in the end-of-life phase more than 4.26107 species.year compared to 1.7 species.year across the overall life-cycle impacts. Several perspective-based circular and sharing economy scenarios were assessed to reveal the benefits of circular collaborative economy applications in leveraging possible ecological burden before, during, and post-mega events in sustainable construction. This research acts as a backbone for future single-sport mega-events to attempt to transition to a carbon-neutral, fully sustainable event with an everlasting legacy.